Membangun Madrasah Ibtidaiyah Unggul: Peran Manajemen Pendidikan Islam bagi Calon Guru MI - Hamdanah, Hamdanah (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study examines the role of Islamic educational management in preparing pre-service teachers of Islamic Elementary School Teacher Education (PGMI) to build excellent Madrasah Ibtidaiyah (MI). Contemporary MI teachers not only serve as instructors but also as learning managers and change agents who require solid managerial competencies. This research aims to analyze PGMI students' understanding of Islamic educational management, identify Islam-based managerial competencies needed, and formulate an integration model of Islamic educational management in developing PGMI students' competencies. Employing a mixed methods approach with explanatory sequential design, the study involved 300 PGMI students for the quantitative phase and 26 informants consisting of students, lecturers, and MI principals for the qualitative phase. Data were collected through questionnaires, in-depth interviews, Focus Group Discussions, classroom observations, and document analysis. Results indicate that the majority of PGMI students (67%) have moderate understanding of Islamic educational management with an average score of 3.2/5.0. Understanding is limited to classroom management aspects while weak in institutional management, reflecting a curriculum gap that allocates only 3.5% of credits for management learning. The research identifies five domains of Islam-based managerial competencies: Planning (Takhthith), Organizing (Tanzhim), Leadership (Qiyadah), Supervision (Riqabah), and Evaluation (Taqwim). As a solution, the study formulates the PRIMA Model (Professional-Religious Integrated Management for MI Teachers) consisting of four components: Integrated Curriculum, Experience-Based Learning, Managerial Character Development, and Holistic Evaluation. This model received high validation from stakeholders with 85% of lecturers, 90% of MI principals, and 88% of students rating it as highly relevant and needed. This research contributes theoretically by enriching Islamic educational management literature from a teacher preparation perspective, practically by providing a blueprint for PGMI curriculum development, and policy-wise for standardizing national PGMI graduate competencies. Implementation of the PRIMA Model is expected to improve the quality of PGMI graduates and subsequently accelerate the transformation of MI towards excellence..